Effects of La-addition to the structure, hydrogen storage, and electrochemical properties of C14 metal hydride alloys. (20th August 2015) - Young, K.; Wong, D.F.; Ouchi, T.; Huang, B.; Reichman, B.
Highlights: La addition to AB2 alloys promotes formation of LaNi phase. LaNi phase facilitates formation and high-rate operation by increasing surface area. LaNi phase causes pulverization and degrades the cycle stability. -40 °C low temperature was much improved with La-addition. Abstract: The structure of a series AB2 metal hydride alloys, in which La substitutes for Zr (Ti12 Zr22.8− x V10 Cr7.5 Mn8.1 Co7.0 Ni32.2 La x Al0.4, x  = 0 to 5), is studied and correlated to various hydrogen storage properties in both gaseous phase and electrochemical systems. La, instead of entering the main Laves phase, forms a LaNi secondary phase which has very limited solubility with other elements. This phase improves activation of both capacity and high-rate dischargeability through a dramatic increase in surface area due to pulverization. The presence of LaNi phase also improves the high-rate dischargeability, facilitating the bulk diffusion of protons through synergetic effects with the main Laves phase. La-content in the alloys also suppresses the TiNi secondary phase due to competition of Ni with the LaNi phase. The lattice constants and unit cell volume of the main C14 phase decreases as more Zr (relatively large) is substituted out, which leads to a less stable hydride with higher equilibrium plateau pressure, higher Δ H, and lower hydrogen storage capacity. With the addition of La in the alloy samples, C14 and LaNi phase abundances increase while C15 and TiNi phase abundances decrease. At −40 °C, the charge-transfer resistance of the La-containing alloys decreases as a result of increased catalytic ability in the main phase. The lowest overall charge-transfer resistance obtained from electrochemical impedance spectroscopy analysis measured at −40 °C is 11 Ω g.